2011
DOI: 10.1590/s0004-282x2011000500016
|View full text |Cite
|
Sign up to set email alerts
|

Brachial plexus surgery: the role of the surgical technique for improvement of the functional outcome

Abstract: Objective:The study aims to demonstrate the techniques employed in surgery of the brachial plexus that are associated to evidence-based improvement of the functional outcome of these patients. Method: A retrospective study of one hundred cases of traumatic brachial plexus injuries. Comparison between the postoperative outcomes associated to some different surgical techniques was demonstrated. Results: The technique of proximal nerve roots grafting was associated to good results in about 70% of the cases. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Zong‐yuan et al (2003) studied the anatomical features of the radial nerve branches innervating the triceps brachii muscle in the upper arm and found that the nerve to the long head had a constant origination point, the proximity of which can be anastomosed with the axillary nerve directly on the same side and had the largest diameter similar to the axillary nerve. The studies of Leechavengvong et al (2003,2006), Witoonchart et al (2003), and Flores (2011) concluded that double innervations using the nerve to the long head of the triceps provided good function of the shoulder and using it was the most reasonable option for double nerve transfers to restore shoulder function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zong‐yuan et al (2003) studied the anatomical features of the radial nerve branches innervating the triceps brachii muscle in the upper arm and found that the nerve to the long head had a constant origination point, the proximity of which can be anastomosed with the axillary nerve directly on the same side and had the largest diameter similar to the axillary nerve. The studies of Leechavengvong et al (2003,2006), Witoonchart et al (2003), and Flores (2011) concluded that double innervations using the nerve to the long head of the triceps provided good function of the shoulder and using it was the most reasonable option for double nerve transfers to restore shoulder function.…”
Section: Discussionmentioning
confidence: 99%
“…A simultaneous transfer of the suprascapular nerve and the axillary nerve yields better results when adequate donors are available (Chuang et al,1995; El‐Gammal and Fathi, 2002; Merrell et al,2001). Recent studies show better outcomes in restoration of deltoid function by combining the transfer of the nerve to the long head of the triceps to the axillary nerve (Leechavengvongs et al,2003,2006; Witoonchart et al,2003; Flores,2011; Lu et al,2012). This new technique has been widely accepted in patients with strong triceps power in order to provide dual muscular reinnervation of the shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of examining the strength in specific muscles, a previous study calculated the average BMRC score of muscle groups in the shoulder, elbow, and wrist to represent the functional outcome after surgery . Evaluation of the motor recovery of multiple muscles would have a better integrated profile and assist surgeons or therapists when making decisions for rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of the elbow flexion remains the most important objective in treating brachial plexus injuries affecting the upper roots (Flores, 2011b). However, elbow flexion is only fully effective if the patient is able to stabilize the movement, which cannot be accomplished if the antagonist muscle cannot be co-activated (Doi et al, 1997;Goubier and Teboul, 2007).…”
Section: Discussionmentioning
confidence: 99%